2015
DOI: 10.1088/0957-4484/27/2/025103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antibacterial activity of caffeic acid phenethyl ester and PLGA nanoparticle formulation by different methods

Abstract: The aim of the present study was to evaluate the antimicrobial activity of nanoparticle and free formulations of the CAPE compound using different methods and comparing the results in the literature for the first time. In parallel with this purpose, encapsulation of CAPE with the PLGA nanoparticle system (CAPE-PLGA-NPs) and characterization of nanoparticles were carried out. Afterwards, antimicrobial activity of free CAPE and CAPE-PLGA-NPs was determined using agar well diffusion, disk diffusion, broth microdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 49 publications
4
75
1
1
Order By: Relevance
“…Mean particle size (Z-Ave), zeta potential (f), polydispersity index (PDI) and surface morphology Z-Ave and f values of the HspNPs were measured with photon correlation spectroscopy using a Zetasizer Nano ZS (Malvern Instruments, Worcestershire, UK) [25]. For the purpose of visualizing surface morphology and size distrubition of nanoparticles, field emission scanning electron microscopy was used (JSM-7001FA, JEOL, Tokyo, Japan) with an acceleration voltage of 10 kV [26]. SEM images were taken after Au coating with magnification of 30.000x.…”
Section: Reaction Yield (Ry) Encapsulation Efficiency (Ee) and Drug mentioning
confidence: 99%
“…Mean particle size (Z-Ave), zeta potential (f), polydispersity index (PDI) and surface morphology Z-Ave and f values of the HspNPs were measured with photon correlation spectroscopy using a Zetasizer Nano ZS (Malvern Instruments, Worcestershire, UK) [25]. For the purpose of visualizing surface morphology and size distrubition of nanoparticles, field emission scanning electron microscopy was used (JSM-7001FA, JEOL, Tokyo, Japan) with an acceleration voltage of 10 kV [26]. SEM images were taken after Au coating with magnification of 30.000x.…”
Section: Reaction Yield (Ry) Encapsulation Efficiency (Ee) and Drug mentioning
confidence: 99%
“…The difference in antibacterial activity of micelles against Gram‐positive ( S. aureus ) and Gram‐negative ( E. coli ) can be correlated with the differences in the cell wall structures of these bacteria. Recently, it was shown that the presence of a higher number of negative charges on the cell wall of the Gram‐negative bacteria ( E. coli ) causes stronger electrostatic interactions with the counter charged micelles . It was reported that E. coli and S. aureus have surface charges of −18.2 mV and −7.13 mV, respectively, indicating that S. aureus bacteria were significantly less negatively charged than E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the shaking water bath was adjusted to 37° and agitation was started at 100 rpm. Samples were withdrawn at specific time intervals and same volume of fresh PBS solution was replaced each time [38] . The AMD concentration was determined on a UV/Vis spectrophotometer at 242 nm [35] .…”
Section: In Vitro Release Of Amd From Csnpsmentioning
confidence: 99%